Mental Strain and its Relationship with the Attitude towards the Immigration of the University Students - Nisreen Ali Abd Ulhasan Al-Jailawi; Khulud Raheem Asfoor (College of Education for Women, 2019)
the appearance and increasing of the young immigration within 2015, the researcher intuition as a mother and part of the society, and the role of the psychological attitude in enabling the individual to make decision, in the light of all the above come up the need for studying this problem. The study aims at finding out: 1. The mental strain of the study sample. 2. The differences in mental strain of the study sample according to the gender, specification, the university, the study (private, not private), and if they have immigrated friends or relatives out of the Iraq. 3. The study sample attitudes towards immigration. 4. The study sample levels of attitudes towards immigration. 5. The differences in the sample attitudes towards immigration according to the gender, specification, the university, the study "private, not private", and if they have immigrated friends or relatives out of the Iraq. 6. The relationship between the mental strain and the sample attitudes towards immigration. The mental strain is the direct influence of the mental fatigue that depends on the individual habits in facing pressures. The attitude towards the immigration is the extend of the preceding acceptance of the university students to immigrate the home and live out for long or short period after reaching complete conviction and insisting. The random stratified sampling method is used to select (300) students of (9) colleges from the university of Baghdad and the college of Dijala. For verifying the study aims the (GHQ-12) scale has been translated to measure the cognitive load and a scale of attitude towards immigration has been constructed according to Osgood method. The validity and reliability of the scales have been ensured. After analyzing the data statistically, the results show that: 1. Decrease the mental strain of the study sample and decrease the level of anxiety, depression, and lack in trust, but there is an increase in the level of social difficulties. 2. There are no statistically significant differences in the mental strain, its dimensions and the independent variables (gender, specification, the university, the study "private, not private", and if they have immigrated friends). However, there are statistically significant differences according to the study type in the favor of not private universities. 3. There are negative attitudes towards the immigration out the Iraq. 4. Only (22%) of the sample have high attitude toward the immigration and (78%) do not show clear attitude towards the immigration. 5. There are no statistically significant differences in the study sample attitudes towards the immigration according to the independent variables. 6. There is no relationship between the mental strain and attitudes towards the immigration out the Iraq. According to the results several suggestions and recommendations set forwards.